Reduction of bearing degradation of 6-switch inverter-fed machine - Wang, Zaixing (2017)
For its excellent power conversion efficiency, pulse width modulation (PWM) converter based variable-frequency drives to control AC machines have been widely used in marine propulsion applications. However, it also leads to early bearing degradation in inverter driven machine due to the transient shaft voltage and high frequency bearing currents resulted from the PWM switching. To reduce the machine bearing current and extend the bearing lifetime, one possible solution is to reduce the common-mode (CM) voltage generated by the three-phase inverter. The dissertation aims to explore different PWM switching strategies to reduce the CM voltage of standard 6-switch inverter. In this dissertation, various PWM techniques in reduction of common mode voltage are theoretically investigated. The conventional space vector PWM is set as the baseline and other PWM methods including discontinuous PWM (DPWM), near state PWM (NSPWM) and active zero space PWM (AZSPWM) are compared with the baseline. The proposed reduced common mode voltage (RCMV) PWM methods significantly reduce CMV from 1/2 Vdc to 1/6 Vdc. In the study, in addition to the CMV characteristics, various practical performance characteristics such as voltage linearity range, inverter output current ripple, total harmonic distortion (THD), and output line-to-line voltage pulse pattern are also analysed. The near state PWM is concluded as the superior RCMV-PWM method since its lower THD level in high modulation index. The study involves mathematical analysis, derivation and computer simulations, the simulation model building process are also given in chapters.